The impact of the COVID-19 pandemic-related quarantine on female sexual behavior: a cross-sectional study in China - Guangyong Li; Puguang Yu; Fen Zhang; Yanlong Xu; Gaiyan Zhou; Xuekang Zhan; Yu Gao; Xiaoli Du; Hetao Liu; Rui He (Scientific Reports, 2022)
Abstract To investigate the impact and factors of home quarantine life on women’s sexual lives and behaviors in different areas of China and analyze the prevalence of female sexual dysfunction (FSD) during the COVID-19 pandemic. We surveyed adult women who had a regular sexual life (including regular masturbation) and had been isolated at home for at least one month during the COVID-19 outbreak using online questionnaires. This survey recovered 678 complete questionnaires after screening. According to the findings, the overall score of the Female Sexual Function Inventory (FSFI) during the pandemic was 21.98 ± 6.38, the frequency of FSD was 61.9%, and the frequencies of FSD in Shanghai, Nanjing, and Ningxia were 60.6%, 75.2%, and 52.2%, respectively. The frequency of FSFI scores and other specific items (Desire, Arousal, Lubrication, Orgasm, Satisfaction, and Pain) varied significantly across the three regions (P < 0.05). The overall frequency of FSD in the masturbation population was 34.4%, which was lower than the frequency of FSD in women having paired sexual intercourse (60.1%) (p < 0.05). Further analysis revealed that the occurrence of FSD during the pandemic was related to different age stages, menopause, mode of delivery, level of anxiety and depression, and sexual lifestyles. The COVID-19 pandemic has had a great impact on people’s spiritual and sexual lives, which are caused by multiple different variables related to both the individual and the environment. We should emphasize the importance of sexual health in epidemics, and having a harmonious and stable sex life will help us survive the boring life of isolation.